2010
DOI: 10.1074/jbc.m110.155119
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved Measurements of Intracellular ATP in the Yeast Saccharomyces cerevisiae using a New Type of Nanobiosensor

Abstract: Adenosine 5-triphosphate is a universal molecule in all living cells, where it functions in bioenergetics and cell signaling. To understand how the concentration of ATP is regulated by cell metabolism and in turn how it regulates the activities of enzymes in the cell it would be beneficial if we could measure ATP concentration in the intact cell in real time. Using a novel aptamer-based ATP nanosensor, which can readily monitor intracellular ATP in eukaryotic cells with a time resolution of seconds, we have pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 43 publications
11
109
0
Order By: Relevance
“…Thus, Brr2 as modeled in the cryo-EM structure could not adopt the autoinhibited state described here, as its loading on U4 snRNA would be in conflict with the autoinhibitory position of the plug. The complex used for cryo-EM analysis disintegrated in an uncharacterized fashion upon addition of 1 mM ATP (Nguyen et al 2015), showing that additional mechanisms must exist to prevent wasteful tri-snRNP disruption in vivo, where ATP levels range between 1 and 2.8 mM (Ozalp et al 2010). Consistent with this proposal, we observed that yeast tri-snRNPs in extracts remain stable in the presence of ATP.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, Brr2 as modeled in the cryo-EM structure could not adopt the autoinhibited state described here, as its loading on U4 snRNA would be in conflict with the autoinhibitory position of the plug. The complex used for cryo-EM analysis disintegrated in an uncharacterized fashion upon addition of 1 mM ATP (Nguyen et al 2015), showing that additional mechanisms must exist to prevent wasteful tri-snRNP disruption in vivo, where ATP levels range between 1 and 2.8 mM (Ozalp et al 2010). Consistent with this proposal, we observed that yeast tri-snRNPs in extracts remain stable in the presence of ATP.…”
Section: Discussionsupporting
confidence: 81%
“…S6). Because cellular ATP concentrations are only about twofold higher than ADP concentrations (62), these data suggest that Rok1 is bound to ADP in vivo, rendering this annealing activity relevant.…”
Section: A2 A2mentioning
confidence: 85%
“…It is not known when during the cycle Dbp5 becomes bound to ATP. As the intracellular concentration of ATP is high (>1 mM) (Ozalp et al 2010), Dbp5 might bind ATP soon after dissociation of ADP. However, because Gle1-IP 6 promotes ATP binding in vitro (Noble et al 2011), Dbp5 might remain in the apo form until it moves from Nup159 to Gle1.…”
Section: Discussionmentioning
confidence: 99%